Konsekuensi Green Trust Terhadap Green Perceived Value, Green Perceived Risk dan Green Repurchase Intention - Lisnaningrum, Destya; Sabihaini, Sabihaini; Ghofar, Abdul (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2020)
This study determine the effect of green perceived value and green perceived risk on green repurchase intention mediated by green trust in customers of The Body Shop products in the Special Region of Yogykarta. The independent variables are green perceived value and green perceived risk. The dependent variable is a green repurchase intention. Green trust is a mediating variable. The population in this study are customers of The Body Shop products. Sample collection is done by area sampling techniques by grouping DIY into 5 groups, namely Bantul, Gunungkidul, Kota Yogyakarta, Kulon Progo, Sleman and the purposive sampling with the criteria of having made at least 2 purchases of The Body Shop products number of 150 respondents. The data analysis method used in this study is structural equation modeling (SEM). The results of this study are If consumers feel the benefits of a product towards the environment is high, it will increase trust and repurchase in the product. If consumers have a negative perception of a product that is high it will reduce trust and reduce interest in repurchasing the product. Consumer trust in products can mediate consumer ratings of the benefits received, negative perceptions and repurchase in the product.